(untitled) (Journal of the College of Education for Women, 2019)
The study showed a significant rise in the proportion of the labor force in agricultureactivity among the detailed economic activities in 1997 with a rate (%28.9), and thendecreased to (%18.8) in 2011, and this belong to the deterioration of agriculture and thetransition to the other economic activities.2- The highest percentage of male’s participation in year 1997 obtained by the activity (A),which is represented by agriculture , where was (%30.0) while the highest percentage offemale’s participation has been brought by the activity (M) which is represented educationwith a rate (% 47.9). while in 2011 that the highest proportion of males’ concentrationobtained by the activity (L) with a rate (%23.1) while the highest proportion females’concentration obtained by the activity (M) with a rate (%37.2).3- The third field (services) came, in the first rank for years 1997 and 2011 with a rate(%58.9), (%74.8) successively, and the reason of this rise belong to transition the workersfrom agriculture and industry to services after the deterioration of agriculture and stoppingmost of state’s factories on working after year 20034- The majority of workers in the districts of the province urban areas are working within theactivities of the third field, which are represented by services and the associated terms, andhad the first rank with the proportion of workers in year 1977 with a rate (%78.3) and thenincreased to (%89.8) in year 2011, while the workers in the rural areas that the field ofagriculture had the first rank for the years 1997 and 2001 with a rate (%72.9) in year 1997and then decreased to (%58.8) in year 2011, and the reason for this decline belong to theorientation of workers in the countryside to work in the services’ activity.